Experimental Study on Flow Boiling Pressure Drop and Flow Instabilities of Reentrant Micro-channels. Issue 6 (1st November 2016) - Deng, D.; Huang, Q.; Wan, W.; Zhou, W.; Lian, Y.
Abstract : Flow boiling pressure drop and flow instabilities of Ω-shaped reentrant copper micro-channels were experimentally explored. Tests were conducted in deionized water and ethanol at inlet subcoolings of 10°C and 40°C, mass fluxes of 125–300 kg/m 2 ·s, and a wide range of heat fluxes and exit vapor qualities. The operational parameters effects, i.e., heat flux, mass flux, inlet subcooling, and coolants, on pressure drop and flow instabilities were systematically explored. The two-phase pressure drop of reentrant micro-channels were found to generally increase monotonically with increasing heat fluxes and exit vapor qualities. Nevertheless, the roles of mass flux and inlet subcooling were dependent on the test coolant.